A glimpse of light in darkness: Performance‐based accountability in Bangladesh public administration. (2nd June 2021) - Shahan, Asif Mohammad; Jahan, Ferdous; Khair, Rizwan
Abstract: In the public administration literature, several studies have been conducted to analyze the performance of the developing countries in embracing the New Public Management (NPM) principles in general. However, limited attention has been paid to explore the experiences of these countries in implementing a performance‐based accountability system, which is an integral part of the NPM movement. This paper analyzes the experience of Bangladesh, wherein 2014, the Government introduced a key performance‐based accountability initiative known as Annual Performance Agreement (APA). In this paper, based on in‐depth qualitative interviews with 42 bureaucrats at different levels and ministries of the Government, we argue that APA has improved the professional accountability of the bureaucracy. Based on this crucial finding, we try to explain why this particular initiative has succeeded whereas previous administrative reform efforts have largely failed. We argue that whereas the past reform efforts targeted broad organizational reforms, the current performance‐based initiatives like APA aimed to bring small‐scale incremental efficiency and effectiveness of bureaucrats. This change in the reform approach has played a pivotal role in ensuring the success of a performance‐based professional accountability system. The model we have developed for categorizing administrative reform efforts in this paper may be used to better understand the success and failure of administrative reform efforts in general and in developing countries in particular.